Election Violence and Voter Turnout in 2019 General Elections: What Role for Political Parties? - Mustapha Salihu; Yahaya Yakubu (European Scientific Journal, ESJ, 2021)
This study examines the incidence of electoral violence and its resultant effects on voter turnout in the 2019 general elections in Nigeria, with the role of political parties as the focal point of discussion. A review of election data shows; voter turnout has been on the decline from 69% in 2003 to 35% in 2019. While a handful of factors could be responsible, the study ascribes its prevalence to the antic’s political parties (incumbent and opposition) and politicians who deliberately deploy violence as an electoral strategy. To account for the relationship between, political parties, electoral violence and voter turn-out, the study builds on theories of voter mobilization in and advanced and emerging democracies. Against this, it concludes in the absence of enduring party-voter relations in Nigeria, political parties and politicians alike, resort to vote buying, mobilization of political thugs and in other times deployment of state coercive apparatus to intimidate opponents all of which culminates into electoral irregularities which has the potency to instigate electoral violence. This in turn has in amongst others adversely affected voter turn-out as rightly observed over five electoral cycles.